ANALISA PENGARUH SERVICE QUALITY TERHADAP LOYALITAS PELANGGAN INDIHOME FIBER DENGAN CUSTOMER SATISFACTION SEBAGAI VARIABEL INTERVENING - Rizki Dika Kristian (Jurnal Strategi Pemasaran, 2018)
The purpose of this research aims to analyze the effects of Service Quality towards Customer Loyalty in Indihome Fiber with Customer Satisfaction as intervening variable. This research was conducted by distributing questionnaires to 100 respondents which are customer of Indihome Fiber Indihome customers who have been at least 1 year of subscription. This research using service quality (X1) variable with indicators Network Quality, Customer Service and Technical Support, Information Quality and Website Information, Security and Privacy, customer satisfaction variable (Y1) with indicators Fulfillment, Pleasure, Relief, customer loyalty variable (Z1) with indicators Say positive things, Recommending to friends, and Continue purchasing, the results showed: (1) service quality influence significantly related to customer satisfaction; (2) service quality affect significantly related to customer loyalty; (3) customer satisfaction has significant impact on customer loyalty.